A riqueza socioemocional e sua influência em uma organização familiar - Dal Ré, Lizandra (2021)
This case study aims to investigate and analyze the presence of socioemotional wealth in a group of family businesses and, based on the results of this analysis, present and propose changes in order to enhance the benefits resulting from the identification of the dimensions of socioemotional wealth that according to the literature it is a resource that generates competitive advantage. The research is characterized as exploratory and of a quantitative and qualitative nature. Two techniques of data collection were used: the first, application of questionnaires for employees of the family group companies to measure their perception of the presence of the dimensions of socioemotional wealth in the group companies, and the second carried out through semi-structured interviews. with family members from three different generations, to identify which of the dimensions of socioemotional wealth are most present in the family group. The theoretical contribution of the study consists in the discussion of socioemotional wealth, with regard to the involvement of the family in the organization and management of the business, taking into account that socioemotional wealth reinforces the sustainability of family businesses. This study broadens the debate about the importance of maintaining socioemotional wealth in family businesses, suggesting that this process contributes to the maintenance of a sustained competitive advantage, from the point of view of family integration. In view of the results, this research contributes to the reduction of the theoretical gaps identified during the literature review, presenting a way to measure the presence of the dimensions of Socioemotional Wealth in family organizations.